Resistência ao cisalhamento de lajes alveolares contínuas em pavimentos a partir do mecanismo de tração diagonal - Rocha, Arthur Lima (2023)
The use of continuous hollow core slabs with structural topping floors has increased in the past few years in the civil construction. By reason of this use, different types of loads can occur on the hollow core slabs units, such as high intensity point loads. In this way, the necessity to understand the shear strength mechanisms of this kind of floor systems with composite elements is essential, because there is a lack of existent literature about situations with continuity and topping on site. For this, validation was carried out based on a test in a continuous situation, using the existing theory. From the verified data, hollow core slabs without topping, with topping and continuous with structural toppings subjected to point loads can have the tension shear mechanism achieved. For this to occur, one must ensure that the prestressing transmission length does not crack, which is facilitated for situations with continuity and details are necessary to maintain the connection between topping and hollow core slab.